An Operations management study on Basecom Incorporated - Capili, Robert Jerome (College of Engineering, 2003)
The company in study is Basecom Incorporated. Its nature of operation is sugar milling. The company has been experiencing decrease in production and this is its main concern as of the moment. The study team applied Operations management techniques and principles to address these concerns. The study team documented the activities that transform the sugarcane to raw sugar. This includes forecasting, quality management, process strategy, location & layout strategy, human resource, supply-chain, inventory scheduling, and maintenance. Every detail on the company's operation function was documented. This include company strategies, processes and activities in production, and the important persons involved in operations. To present these, the study team used figures, graphs, process maps, and flow charts to provide better illustration of operations. The project then, identified the possible problems after interviews with the plant consultant, process supervisor, plant personnel and brainstorming. The streamline diagnostic diagram was used to provide visual aid in identifying the areas that needed most attention. Here, factors affecting variations and losses in production were analyzed with their corresponding causes and effects. After identifying specific problem areas/s, Recommendations were proposed by the study team. Quantitative and qualitative considerations were taken into account in formulating and evaluating alternatives.